2016
DOI: 10.4028/www.scientific.net/amm.844.50
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Based Analysis of Reconfigurable Manufacturing System Configurations

Abstract: Nowadays, manufacturers seek customers’ satisfaction by increasing products variety and customization while striving for agility and productivity. To remain competitive, companies must design manufacturing systems that not only produce high-quality products at low cost, but also respond to market changes in an economical way. One of the critical problems of manufacturing systems design is to decide which of possible configurations is the most advantageous for a company. This article presents the possibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The literature acknowledges the importance of applying digital technologies such as CPSs in RMSs for addressing the dynamic behaviour of materials and information. It suggests that applying a CPS in the CA of RMSs contributes to rapid response and improves the productivity, responsiveness and cost of manufacturing systems [27,39,66]. However, recent research efforts have overlooked material handling, an essential aspect for addressing dynamic behaviour of RMS [67].…”
Section: Identi Ed Gap and Research Questionsmentioning
confidence: 99%
“…The literature acknowledges the importance of applying digital technologies such as CPSs in RMSs for addressing the dynamic behaviour of materials and information. It suggests that applying a CPS in the CA of RMSs contributes to rapid response and improves the productivity, responsiveness and cost of manufacturing systems [27,39,66]. However, recent research efforts have overlooked material handling, an essential aspect for addressing dynamic behaviour of RMS [67].…”
Section: Identi Ed Gap and Research Questionsmentioning
confidence: 99%
“…Moreover, it must be designed for reconfiguration when necessary. This reconfiguration requires installation cost and cost in the start-up phase, characterized by malfunctions and breakdowns of these machines [8].…”
Section: Reconfigurable Manufacturing Systemsmentioning
confidence: 99%
“…On the other hand, simulation techniques are considered powerful and supportive when designing and evaluating manufacturing systems [5]. In a broad sense, simulation can be described as an imitation or replica of the operations of a real process or production system over time [16]. To facilitate the simulation process and computing performance, in DES models, the state variables only change at specific discrete points of time when significant events occur, resulting from activity times and delays [17].…”
Section: Reconfigurable Manufacturing Systems and Discrete-event Simu...mentioning
confidence: 99%
“…Previous studies have used DES to support the design and management of RMS in different ways. Studies such as [16] and [19] have employed DES to model and analyze different RMS configurations. Such studies concluded that DES facilities the modelling process and the sequencing of the operations when comparing different RMS configurations.…”
Section: Reconfigurable Manufacturing Systems and Discrete-event Simu...mentioning
confidence: 99%